p53 Rather Than β-Catenin Mediated the Combined Hypoglycemic Effect of Cinnamomum cassia (L.) and Zingiber officinale Roscoe in the Streptozotocin-Induced Diabetic Model - Ayuob, Nasra; Al-Shathly, Mona Ramadan; Bakhshwin, Abdulaziz; Al-Abbas, Nouf Saeed; Shaer, Nehad A; Al Jaouni, Soad; Hamed, Walaa H. E. (Frontiers in Pharmacology, 2021)
Background: The hypoglycemic, insulin- enhancing and antioxidant effects of ginger and cinnamon were previously confirmed in experimental and human studies; however, the effect of combined administration of them was not thoroughly investigated until now. Objectives: This study was designed to assess the antidiabetic effect of combined ginger (Gingiber officinale) and cinnamon (Cinnamomum cassia) administration in Streptozotocin (STZ)-induced diabetic Spraque-Dawley rats compared to metformin, and to explain the mechanism behind this effect. Materials & methods: STZ was utilized to induce diabetes mellitus in male Spraque-Dawley rats. The effect of combined ginger and cinnamon was compared to that of metformin-treated and untreated diabetic rats. Measurements of fasting blood glucose level (BGL), the total anti-oxidant capacity (TAC), serum insulin and HOMA-IR and HOMA-β cell were performed. Gene expression of β-catenin and p53 in pancreatic tissue was assessed using RT-PCR. Assessment of the pancreatic histopathological alternation was performed using routine and immunohistochemical techniques. Results: BGL significantly decreased (p=0.01) while serum insulin and TAC significantly increased (p<0.001) in metformin-and ginger plus cinnamon-treated groups in comparison to the untreated diabetic group. HOMA-β-cell index significantly increased (p=0.001) in ginger plus cinnamon indicating their enhancing effect on insulin section in diabetic conditions. Gene expression of p53 was significantly up-regulated (p<0.001) while β-catenin was insignificantly down-regulated (p=0.32) in ginger plus cinnamon-treated groups. Insulin immunoexpression in β cells showed a significant increase (p=0.001, p=0.004) in metformin- and ginger plus cinnamon-treated groups. Conclusion: The combined administration of ginger and cinnamon has a significant hypoglycemic and antioxidant effect in STZ-induced diabetes mellitus mostly through enhancing repair of islet cells mediated via up-regulation of pancreatic p53 expression. Therefore, testing this effect in diabetic patients is recommended.